The effect of encapsulation of cardiac stem cells within matrix-enriched hydrogel capsules on cell survival, post-ischemic cell retention and cardiac function - Mayfield, Audrey E. (2013)
Transplantation of ex vivo proliferated cardiac stem cells (CSCs) is an emerging therapy for ischemic cardiomyopathy but outcomes are limited by modest engraftment and poor long-term survival. As such, we explored the effect of single cell microencapsulation to increase CSC engraftment and survival after myocardial injection. Transcript and protein profiling of human atrial appendage sourced CSCs revealed strong expression the pro-survival integrin dimers αVβ3 and α5β1- thus rationalizing the integration of fibronectin and fibrinogen into a supportive intra-capsular matrix. Encapsulation maintained CSC viability under hypoxic stress conditions and, when compared to standard suspended CSC, media conditioned by encapsulated CSCs demonstrated superior production of pro-angiogenic/cardioprotective cytokines, angiogenesis and recruitment of circulating angiogenic cells. Intra-myocardial injection of encapsulated CSCs after experimental myocardial infarction favorably affected long-term retention of CSCs, cardiac structure and function. Single cell encapsulation prevents detachment induced cell death while boosting the mechanical retention of CSCs to enhance repair of damaged myocardium.